Defending - Harvey, Gill. (Tulsa, OK EDC Publishing Company, 1996)
Takes the view that all players are defending when the opponent has the ball. It covers all the skills needed to win the ball back, from tackling to team tactics.
5 - 9
Keywords: Soccer